High-Discrimination Circular Polarization Detection Based on Dielectric-Metal-Hybrid Chiral Metamirror Integrated Quantum Well Infrared Photodetectors - Jinyong Shen; Tianyun Zhu; Jing Zhou; Zeshi Chu; Xiansong Ren; Jie Deng; Xu Dai; Fangzhe Li; Bo Wang; Xiaoshuang Chen; Wei Lu (Sensors, 2022)
Circular polarization detection enables a wide range of applications. With the miniaturization of optoelectronic systems, integrated circular polarization detectors with native sensitivity to the spin state of light have become highly sought after. The key issues with this type of device are its low circular polarization extinction ratios (CPERs) and reduced responsivities. Metallic two-dimensional chiral metamaterials have been integrated with detection materials for filterless circular polarization detection. However, the CPERs of such devices are typically below five, and the light absorption in the detection materials is hardly enhanced and is even sometimes reduced. Here, we propose to sandwich multiple quantum wells between a dielectric two-dimensional chiral metamaterial and a metal grating to obtain both a high CPER and a photoresponse enhancement. The dielectric-metal-hybrid chiral metamirror integrated quantum well infrared photodetector (QWIP) exhibits a CPER as high as 100 in the long wave infrared range, exceeding all reported CPERs for integrated circular polarization detectors. The absorption efficiency of this device reaches 54%, which is 17 times higher than that of a standard 45° edge facet coupled device. The circular polarization discrimination is attributed to the interference between the principle-polarization radiation and the cross-polarization radiation of the chiral structure during multiple reflections and the structure-material double polarization selection. The enhanced absorption efficiency is due to the excitation of a surface plasmon polariton wave. The dielectric-metal-hybrid chiral mirror structure is compatible with QWIP focal plane arrays.